Chitin Foils and Coatings Prepared from Ionic Liquids. Issue 11 (29th June 2016) - Walther, Patrick; Ota, Antje; Müller, Alexander; Hermanutz, Frank; Gähr, Frank; Buchmeiser, Michael R.
Abstract : Designed phosphonium‐ and imidazolium‐based ionic liquids are used as solvents for chitin and the influence of the cation on the solution process has been evaluated. In particular imidazolium carboxylate‐based ILs are turned out to be appropriate solvents for chitin and allowed for the production of foils and coatings on both fabrics and foams. Abstract : Chitin and its deacetylated derivative, chitosan, are nontoxic, antibacterial, biodegradable, and biocompatible biopolymers. Due to these properties, they are widely used for biomedical applications such as scaffolds for tissue engineering, wound dressings, separation membranes and antibacterial coatings. Unfortunately, there is still a lack of suitable solvent systems for the direct processing of chitin, e.g., into films and coatings. Such solvents must be nontoxic, noncorrosive, nondegrading, and allow for high chitin concentrations. Here, the potential of designed ionic liquids (IL) as solvents for chitin is outlined. Phosphonium‐ and imidazolium‐based ILs are synthesized, characterized and the influence of the cation on the solution process has been evaluated. It is shown that particularly imidazolium carboxylate‐based ILs are appropriate solvents for chitin and are suitable for the production of foils and coatings on both fabrics and foams.